Chemical profiling, antioxidant potential, molecular docking and molecular dynamic simulation of essential oil constituents of four Curcuma species - Gadnayak, Ayushman; Nayak, Ananya; Mohanty, Swagat; Dash, Biswabhusan; Sahoo, Ambika; Jena, Sudipta; Panda, Pratap Chandra; Ray, Asit; Nayak, Sanghamitra (Edelweiss Applied Science and Technology, 2025)
This study presents an extensive phytochemical characterization, antioxidant activity, and in silico analysis of the essential oils derived from the rhizomes of Curcuma amada, Curcuma angustifolia, Curcuma caesia, and Curcuma zedoaria. Gas Chromatography-Mass Spectrometry (GC-MS) analysis demonstrated species-specific variations, with C. amada characterized by major constituents such as myrcene, β-pinene; C. angustifolia by velleral, germacrone, and (2E,6Z)-Farnesol; C. caesia by trans-β-elemenone, curzerenone; whereas C. zedoaria by curzerenone, β-eudesmol acetate, 1,8-cineole. In vitro experiments revealed significant antioxidant capacity in all species, especially in C. angustifolia and C. caesia (DPPH, IC50 = 31.2 ± 0.3 µg/mL and FRAP, EC50 = 23.1 ± 0.2 µg/mL) and (DPPH, IC50 = 39.8 ± 0.5 µg/mL and FRAP, EC50 = 27.0 ± 0.4 µg/mL). In silico docking of primary ingredients against xanthine oxidase revealed sesquiterpenes, including germacrone (–6.5 kcal/mol) and velleral (–6.2 kcal/mol), as effective inhibitors, corroborated by molecular dynamics simulations demonstrating persistent protein-ligand interactions. Curcuma rhizome essential oils show potential as natural antioxidants and xanthine oxidase inhibitors, suggesting their potential in managing oxidative stress-related disorders.